Atractylenolide III alleviates sepsis-mediated lung injury via inhibition of FoxO1 and VNN1 protein - Fu,Ji-ding (2021)
ABSTRACT Purpose: To evaluate the influence of atractylenolide (Atr) III on sepsis-induced lung damage. Methods: We constructed a mouse sepsis model through cecal ligation and puncture. These mice were allocated to the normal, sepsis, sepsis + Atr III-L (2 mg/kg), as well as Atr III-H (8 mg/kg) group. Lung injury and pulmonary fibrosis were accessed via hematoxylin-eosin (HE) and Masson’s staining. We used terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and flow cytometry for detecting sepsis-induced lung cell apoptosis. The contents of the inflammatory cytokines in lung tissue were measured via enzyme-linked immunosorbent assay (ELISA). Results: Atr III-H did not only reduce sepsis-induced lung injury and apoptosis level, but also curbed the secretion of inflammatory factors. Atr III-H substantially ameliorated lung function and raised Bcl-2 expression. Atr III-H eased the pulmonary fibrosis damage and Bax, caspase-3, Vanin-1 (VNN1), as well as Forkhead Box Protein O1 (FoxO1) expression. Conclusions: Atr III alleviates sepsis-mediated lung injury via inhibition of FoxO1 and VNN1 protein.